2011
DOI: 10.1002/adma.201103605
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Left‐Handed Metal Microcoil from Spiral Vessel of Vascular Plant

Abstract: Silver microcoil is fabricated through a biotemplating process combined with electroless plating. Spiral vessels in Lotus root are employed as a biotemplate because of their left-handed coil structure. The silver microcoil exhibits a solenoidal microcoil showing self-inductance in the level of picohenry, which could be applied for electromagnetic-responsive materials in the high-frequency region such as millimeter waves or terahertz waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 25 publications
0
68
0
Order By: Relevance
“…Examination of the fossil records of primitive vascular plants also shows evidence of coiled structures, some of which clearly appear to be left-handed [see for example the image of a vascular strand of Cooksonia pertoni in the paper by Edwards et al (1992)]. Recently, the left-handed coils isolated from lotus plants (Nelumbo nucifera) have been used as templates to prepare silver-coated conducting microcoils (Kamata et al 2011). No right-handed coils were observed in these or other species …”
Section: Resultsmentioning
confidence: 99%
“…Examination of the fossil records of primitive vascular plants also shows evidence of coiled structures, some of which clearly appear to be left-handed [see for example the image of a vascular strand of Cooksonia pertoni in the paper by Edwards et al (1992)]. Recently, the left-handed coils isolated from lotus plants (Nelumbo nucifera) have been used as templates to prepare silver-coated conducting microcoils (Kamata et al 2011). No right-handed coils were observed in these or other species …”
Section: Resultsmentioning
confidence: 99%
“…These helical silicas are also promising hard templates for the preparation of helical nanowires composed of metals [12][13][14][15] or other compositions that may possess unique optical, 16,17 electromagnetic 9,18 or other properties. Efforts to understand the formation mechanism of these helical nanostructures provide additional insights into the interplay of the thermodynamics and kinetics of the assembly of structure-directing surfactants and inorganic silicate species 1,2,19,20 and may also lead to the design and synthesis of additional novel selfassembled nanomaterials with controllable mesostructures and morphologies, allowing for innovative applications.…”
Section: Introductionmentioning
confidence: 99%
“…Helical mesoporous silicas [1][2][3][4][5][6][7][8][9][10][11] are analogous to the self-assembled helical biomaterials in nature and have attracted a substantial amount of attention. These helical silicas are also promising hard templates for the preparation of helical nanowires composed of metals [12][13][14][15] or other compositions that may possess unique optical, 16,17 electromagnetic 9,18 or other properties.…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions coordinated by the phosphates of the DNA molecule (Figure 4a) was reduced to atomic silver creating silver nanoparticles (Figure 4b) which served as growth points for further metallization (Figure 4c). Kamata et al have shown that it is possible to use a similar approach to create optically active material by metallization of biotemplates such as the algae Spirulina 7 or spiral plant structures 8 with interesting resonances in the THz region. Biotemplating has also been expanded to conducting polymers, such as polypyrrole onto DNA 9 , polyaniline on DNA 10 and polyaniline onto amyloid fibers 11 .…”
Section: Biotemplatingmentioning
confidence: 99%
“…Kamata et al has described how coiled cellulose structures from lotus roots can be turned into THz antennas 8 and Agarwal et al has used a layer by layer approach to coat cellulose structure with conducting polymers 78 . Inspired by these works we pursued a path in PAPER VII where helical cellulose based structures were coated with PEDOT-S in a two-step process as depicted in Figure 32.…”
Section: Carbohydrate Scaffoldmentioning
confidence: 99%